Potential Role of Chemokines in Fracture Repair - Edderkaoui, Bouchra (Frontiers in Endocrinology, 2017)
Chemokines are a family of small cytokines that share a typical key structure that is stabilized by disulfide bonds between the cysteine residues at the NH2-terminal of the protein, they are secreted by a great variety of cells in several different conditions. Their function is directly dependent on their interactions with their receptors. Chemokines are involved in cell maturation and differentiation, infection, autoimmunity, cancer and, in general, in any situation where immune components are involved. However, their role in post-fracture inflammation and fracture healing is not yet well established. In this review paper, we will discuss the response of chemokines to bone fracture and their potential roles in post-fracture inflammation and healing based on data from our studies and from other previously published studies.